A STUDY ON THE REPUTATION RULES OF CORPORATE REPUTATION RESEARCH RESULTS AND THEIR COMPLIANCE WITH EKŞISÖZLÜK USER COMMENTS (Third Sector Social Economic Review, 2018)
Reputation is seen as an element that affects perceptions towards individuals, institutions and organizations in a positive way, but it is considered as a whole of positive qualities that provide financial returns by supporting investments and increasing revenues and also providing reliability, respectability and loyalty. Therefore, reputation as an element of such importance plays a key role in the success of different researches as well as being their main theme. In this context, the aim of the study is to determine whether the research conducted on corporate reputation is compatible with the reputation indicators and social media comments on the subject in the literature. In this direction, as a result of the research, the comments about the people and brands that are considered to be reputable were subjected to a mutual evaluation selected among the studies “Turkish Reputation Index Survey” and “Business People Reputation Survey”, rules of reaching a respectable position and social media platforms. It is expected that the study will provide opportunities for social media users to determine the extent to which their views reflect or do not reflect the scientific research results, research companies to review their samplings and to test the reliability of platforms such as ekşisözlük.
Keywords: Reputation; Public Relations; Corporate Reputation Research; Rules of Reputation; Ekşisözlük